Crecimiento, produccion y calidad de frutos en limeros "persa" sobre 11 portainjertos - Piña Dumoulin, G.J.=700 1 Gaston Laborem, E.; Monteverde, E.E.; Magaña Lemus, S.
(Es, En)
Ilus., 20 ref.
Keywords: CITRUS; CRECIMIENTO; PRODUCCION; CALIDAD; PRODUCTIVIDAD; VENEZUELA